Observational Study of Tissue Acquisition Turnaround Time for Commercial Comprehensive Genomic Profiling in Solid Tumors. (11th September 2019) - Krigsfeld, Gabriel; Roth, Aleeza; Cooper, Maureen; Smith, Liisa; Iyer, Radhika; Brown, Adam; Pratt, James; Truesdell, John; Schwartz, Joshua
Abstract: Introduction: Increased development and use of next-generation sequencing in clinical diagnostics has revolutionized precision medicine. Steps prior to a specimen arriving at a diagnostic facility, including pathological evaluation, are crucial parameters determining specimen quality and success of comprehensive genomic profiling (CGP). This observational study identified factors that may influence tissue acquisition for commercial CGP in clinical oncology. Methods: Data were collected from deidentified patients (n = 63) from select US pathology labs enrolled in a Foundation Medicine (FMI) early access program for the CGP test FoundationOne CDx (Foundation Medicine). A representative substudy cohort (n = 20) with qualitative information available was selected. Lab visit frequency by FMI was monitored for 42 cases. Tissue acquisition turnaround time (TA-TAT) was separated into stages: (1) tissue request to pathology lab acknowledgment, (2) pathology lab acknowledgment to tissue pathology review, (3) tissue pathology review to packaging, and (4) packaging to tissue arriving at FMI. Results: Median TA-TAT for the total population was 5.0 days (range, 0-27.0) and 3.5 days for the substudy cohort (range, 1.0-11.0). The duration of each TA-TAT stage was evaluated separately and varied between labs (0%-71.4% of total TA-TAT). TA-TAT was longer for unstained slides compared with formalin-fixed, paraffin-embedded (FFPE) tissue blocks. There was a trend for decreased TA-TAT when stages 1 and 2 occurred on the same day versus different days. For the cases with lab-visit frequency reported, those with biweekly visits had shorter TA-TAT (biweekly: n = 12, median = 2.0, 2.5th-97.5th percentile range, 0.3-5.7 days; single visit: n = 30, median = 5.5, 2.5th-97.5th percentile range, 0.7-13.1 days). Conclusions: Understanding and optimizing the tissue acquisition workflow may reduce TA-TAT, thereby facilitating report delivery and subsequent treatment guidance to patients. Funding: Bristol-Myers Squibb. Professional medical writing and editorial assistance was provided by Katerina Pipili, PhD, and Jay Rathi, MA, of Spark Medica Inc, funded by Bristol-Myers Squibb.